HUBUNGAN PERHATIAN ORANGTUA DENGAN PERILAKU MORAL PADA PESERTA DIDIK FAE F DI SMAN 16 PADANG - Aprillia, Denisa (EDUTECH, 2025)
Abstrak.Penelitian ini dilatarbelakangi oleh adanya peserta didik yang berbohong kepada guru, adanya peserta tidak mengerjakan tugas, adanya peserta didik ribut di kelas, adanya peserta didik yang membeda-bedakan teman, adanya peserta didik yang acuh tak acuh Ketika guru menjelaskan, adanya peserta didik melawan pada guru, adanya peserta didik membolos saat jam pelajaran, adanya peserta izin sakit karena ingin libur sekolah. Tujuan penelitian ini adalah mendeskripsikan: 1) Perilaku moral peserta didik, 2) Perhatian orang tua, 3) Hubungan antara perhatian orang tua dengan perilaku moral peserta didik. Penelitian ini dilakukan dengan menggunakan metode deskriptif kuantitatif dengan analisis korelasi. Populasi penelitian ini adalah peserta didik Fase I SMA N 16 Padang yang berjumlah 179 orang peserta didik. Teknik instrumen yang digunakan angket. Pengambilan sampel ini dilakukan dengan Teknik Simple random sampling yaitu sebanyak 124 orang peserta didik yang menjadi sampel penelitian. Teknik analisis data yang digunakan adalah presentase dan uji korelasi dengan mengunakan aplikasi spss. Hasil penelitian ini menujukan bahwasanya hubungan perhatian orang tua dengan perilaku moral pada peserta didik Fase F di SMA N 16 Padang dapat di ambil kesimpulan sebagai berikut: 1) Perhatian orang tua peserta didik berada pada kategori cukup tinggi. 2) Perilaku moral peserta didik berada pada kategori cukup tinggi. 3)Terdapat hubungan antara perhatian orang tua dan perilaku moral peserta didik di Fase F SMA N 16 Padang adalah sebesar 0,124 dengan koefisien hubungan yang cukup kuat.Keyword: Perhatian orangtua,Perilaku moral THE RELATIONSHIP OF PARENTAL ATTENTION AND MORAL BEHAVIOR IN PHASE F STUDENTS AT SMAN 16 PADANGAbstractThis research was motivated by the existence of students who lied to the teacher, there were students who did not do their assignments, there were students who made noise in class, there were students who discriminated against their friends, there were students who were indifferent. When the teacher explained, there were students who fought against each other. teachers, there are students skipping classes during class time, there are participants taking sick leave because they want to take a break from school. The aim of this research is to describe: 1) Students' moral behavior, 2) Parents' attention, 3) The relationship between parents' attention and students' moral behavior. This research was conducted using quantitative descriptive methods with correlation analysis. The population of this study was Phase I students of SMA N 16 Padang, totaling 179 students. The instrument technique used for this sampling questionnaire was carried out using a simple random sampling technique, namely 124 students who were the research sample. The data analysis techniques used are percentage and correlation tests using the SPSS application. The results of this research show that the relationship between parental attention and moral behavior in Phase F students at SMA N 16 Padang can be drawn as follows: 1) The attention of students' parents is in a fairly high category. 2) Students' moral behavior is in a fairly high category. 3) There is a relationship between parental attention and students' moral behavior in Phase F SMA N 16 Padang, which is 0.124 with a fairly strong relationship coefficient. Based on the results of this research, it is recommended to guidance and counseling teachers that students be able to improve moral behavior regarding especially telling the truth, doing the right thing, acting fairly, and brave behavior. Pay attention to students' parents so that students' moral behavior becomes higher.